USE OF HERBAL SUPPLEMENTS AND POTENTIAL DRUG INTERACTIONS IN CANCER PATIENTS: A CROSS-SECTIONAL INVESTIGATION. - Rao T, Nageswara; Munikumar K; Vangoori, Yakaiah; Sayana, Suresh Babu; Anthireddy, Srinivas (Student’s Journal of Health Research Africa, 2025)
Background The use of herbal supplements among cancer patients has become increasingly prevalent, raising concerns about potential drug interactions that may compromise treatment outcomes and patient safety. Although herbal supplements are often perceived as natural and harmless, they can interact with cancer therapies, potentially altering drug metabolism and efficacy. Objective This study aimed to evaluate the prevalence, types, and patterns of herbal supplement use among cancer patients, assess potential drug interactions with prescribed cancer treatments, and determine the level of awareness and communication regarding supplement use. Methods A descriptive cross-sectional study was conducted at the Konaseema Institute of Medical Sciences and Research Foundation, Amalapuram, from January to June 2023. A structured questionnaire was used to survey 200 adult cancer patients undergoing active treatment. Descriptive statistics and logistic regression analysis were used to evaluate associations. Results Of the 200 patients, 60% reported using herbal supplements during cancer treatment. The most commonly used supplements were St. John’s Wort (20%), Ginger (17.5%), and Turmeric (12.5%). 25% of patients experienced potential herb-drug interactions, including increased toxicity (15%) and reduced treatment efficacy (10%). Only 35% of patients disclosed herbal supplement use to their healthcare providers, while 65% did not, primarily due to perceived irrelevance or fear of disapproval. Conclusion A substantial proportion of cancer patients use herbal supplements alongside prescribed treatments, often without informing their healthcare providers. This practice poses risks of adverse drug interactions and reduced therapeutic efficacy. Recommendations Cancer care providers should integrate routine inquiry about herbal supplement use into patient assessments. Increased patient education is essential to help patients understand the potential risks and make informed decisions. Improved communication and awareness can enhance treatment safety and outcomes.